Determining the Carrot Volume via Radius and Length Using ANN - ÃƒÂ–rnek, Mustafa Nevzat; Kahramanli, Humar (International Journal of Intelligent Systems and Applications in Engineering, 2018)
In this study a total of 464 carrots were taken from KaÅÄ±nhanÄ±, where the most carrots are produces in Turkey. The length and radiuses with an interval of 5 cm and volume were measured and recorded. Three different Artificial Neural Network models: BP, LM and PUNN were designed for predicting the carrot volume. To assess the success of the system, statistical measures such as Root Mean Squared Error, Mean Absolute Error and R2 were used. The results were showed that all three methods are successful in this problem, while LM and PUNN seems bit.